Relaxations and nano-phase-separation in ultraviscous heptanol-alkyl halide mixture - VIJ, JAGDISH (My University, 2007)
To gain insight into the effects of liquid-liquid phase separation on molecular relaxation behavior we have studied an apparently homogeneous mixture of 5-methyl-2-hexanol and isoamylbromide by dielectric spectroscopy over a broad temperature range. It shows two relaxation regions, widely separated in frequency and temperature, with the low-frequency relaxation due to the alcohol and the high-frequency relaxation due to the halide. In the mixture, the equilibrium dielectric permittivity s of the alcohol is 41% of the pure state at 155.7 K and s of isoamylbromide is ~86% of the pure state at 128.7 K. The difference decreases for the alcohol component with decreasing temperature and increases for the isoamylbromide component. The relaxation time of 5-methyl-2-hexanol in the mixture at 155.7 K is over five orders of magnitude less than in the pure state, and this difference increases with decreasing temperature, but of isoamylbromide in the mixture is marginally higher than in the pure liquid. This shows that the mixture would have two Tg's corresponding to its of 103 s, with values of ~121 K for its 5-methyl-2-hexanol component and ~108 K for its isoamylbromide component. It is concluded that the mixture phase separates in submicron or nanometer-size aggregates of the alcohol in isoamylbromide, without affecting the latter's relaxation kinetics, while its own s and decrease markedly
PUBLISHED
Keywords: Electronic & Electrical Engineering